Laundry wastewater treatment by peroxi-coagulation - Nayir, Tulin Yilmaz; Dinc, Ozge; Kara, Serdar; Akyol, Abdurrahman; Dimoglo, Anatoli (Desalination Publ, 2020)
Peroxi-coagulation (PC) process was developed with iron anodes and carbon-polytetrafluoroethylene cathodes for the treatment of laundry wastewater (LWW). The effect of operating conditions as pH, current density and temperature were investigated by response surface modeling. Whereas temperature change did not affect the reaction, pH change dominated it especially between pH 5-7 causing an effective coagulation process. The model was devoted to maximizing the removal of chemical oxygen demand (COD), methylene blue substances (MBAS) and total phosphorus (TP) and to minimizing total residual iron (TFe) concentration in the treated wastewater. Complete TP removal and high removal efficiencies in terms of COD and MBAS were provided at optimal operation conditions (pH 7, current density 45 mA/cm(2) and temperature: 25 degrees C). During the PC process H2O2 and S2O82- production was observed. According to the results, H2O2 concentration was stable during the process after a certain increment; however, persulfate production reached maximum value when surfactant (namely: linear alkylbenzene sulfonate) concentration was almost minimum in the bulk. In the PC process, both the oxidation with possibly formed radicals (i.e. (OH)-O-center dot and SO4-center dot) and the coagulation with iron precipitation are responsible for the LWW treatment.
Keywords: Peroxi coagulation; Laundry wastewater; Response surface modeling; Surfactant; Persulfate